Cyclodextrin in Vaccines: Enhancing Efficacy and Stability - Gamze Varan (MDPI AG, 2023)
Cyclodextrins, a family of cyclic oligosaccharides, have received considerable interest in the field of pharmaceuticals due to their unique molecular structure and versatile properties. In the context of vaccines, cyclodextrins can effectively encapsulate antigens, ensuring their protection from degradation and improving their immunogenicity. Cyclodextrins offer stability advantages to vaccines by preventing the degradation of labile vaccine components during storage and transportation. Furthermore, cyclodextrins can serve as adjuvants, potentiating the immune response triggered by vaccines. Their unique structure and interaction with the immune system enhance the recognition of antigens by immune cells, leading to an improved activation of both innate and adaptive immune responses. This adjuvant effect contributes to the development of robust and long-lasting immune protection against targeted pathogens. Owing to the distinctive attributes inherent to nanoparticles, their integration into vaccine formulations has assumed an imperative role. Through the encapsulation of vaccine antigens/adjuvants within cyclodextrin nanoparticles, the potency and stability of vaccines can be notably enhanced. In particular, the capacity of amphiphilic cyclodextrins to form nanoparticles through self-assembly without surfactants or co-solvents is a captivating prospect for their application as carrier systems for antigens. In conclusion, cyclodextrins present a promising platform for enhancing the efficacy and stability of vaccines. Their ability to encapsulate antigens, stabilize labile vaccine components and act as adjuvants demonstrates their potential to revolutionize vaccine formulation and delivery. Further research and development in this field will facilitate the translation of cyclodextrin-based vaccine technologies into practical and impactful immunization strategies, ultimately benefiting global health and disease prevention.